Investigation on erosion-wear behaviors of high-chromium cast iron with high nitrogen content in salt–sand slurry. (21st August 2019) - Lu, Fugang; Wei, Shizhong; Xu, Liujie; Zhou, Yucheng; Wang, Fangfang; Yang, Yanping; Wang, Xiaodong
Abstract: High-chromium cast iron with high nitrogen content was prepared using a vacuum-induction barotropic melting furnace, and the erosion-wear behaviors of high-chromium cast iron with high nitrogen content were investigated with a rotary erosion-wear tester in salt–sand slurry. The corrosion performance of experimental materials in salt solution was evaluated by the potentiodynamic polarization curves and electrochemical impedance spectra. Results show that the actual phase structure of high-chromium cast iron with high nitrogen content is: α + γ + Cr2 (C, N) + M7 C3 +M23 C6 . The relative wear resistance of high-chromium cast iron with high nitrogen content can reach 1.48 times that of high chromium cast iron. The erosion-wear morphologies are mainly ploughing, indentation, large chips and removal of extruded lips. High-chromium cast iron with high nitrogen content has better mechanical properties and corrosion resistance than high-chromium cast iron, decreasing the synergism of corrosion and wear. Therefore, high-chromium cast iron with high nitrogen content has lower erosion-wear rate.